Experimental and performance analysis of non-line-of-sight (NLOS) localization methodology - Chan, Shi Mei (2016)
As the Global Positioning System (GPS) does not work in the indoor environment due to strong signal attenuation and dense multipath effects. Thus, indoor localization system is necessary.